THE ROLE OF DIGITAL TECHNOLOGIES IN THE DRAFTING OF LEGAL ACTS - Максудбой Садиков (Modern American Journals, 2026)
This article examines the role of circus technologies in the drafting of legal documents, highlights the main opportunities and technical and ethical challenges, as well as potential directions for development in the future. Particular attention is paid to the ethical framework of management, the prospects of legal technologies. The article argues that successful implementation depends on responsible governance, legal oversight, and effective human-AI collaboration.
Keywords: Drafting of legal documents, legal technologies, ethics of artificial intelligence, natural language processing.